2022
DOI: 10.1021/acsami.1c25178
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Stable Zinc-Ion Storage Performance of Manganese Oxides by Synergistic Engineering of the Interlayer Structure and Interface

Abstract: Manganese oxide is a promising cathode material for rechargeable aqueous zinc-ion batteries (ZIBs). However, the low electronic conductivity and unstable structure evolution of manganese materials often result in poor rate performance and rapid capacity decay. Herein, we design N-doped Na2Mn3O7 (N-NMO) by combining sodium preintercalation and nitridation treatment strategies to stabilize the crystalline structure and reaction interface. Sodium preintercalation not only enlarges the interlayer distance for fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…39,40 The proportion of pseudocapacitance at different scan rates can be calculated according to i = k 1 v + k 2 v 1/2 , in which k 1 v and k 2 v 1/2 are related to pseudocapacitance and the diffusion process, repspectively. 41,42 The proportion of pseudocapacitance at the scan rates of 0.2−3 mV s −1 were calculated to be 71.6−92.2% (Figure 5c,d), which confirm again that Na + in the FPS/GPNC electrode is a pseudocapacitive-dominated process. Such a high proportion of pseudocapacitance endows FPS/GPNC with superior rate performance.…”
Section: Study Of Diffusion Kinetics Of the Fps/gpnc Electrodesupporting
confidence: 57%
See 1 more Smart Citation
“…39,40 The proportion of pseudocapacitance at different scan rates can be calculated according to i = k 1 v + k 2 v 1/2 , in which k 1 v and k 2 v 1/2 are related to pseudocapacitance and the diffusion process, repspectively. 41,42 The proportion of pseudocapacitance at the scan rates of 0.2−3 mV s −1 were calculated to be 71.6−92.2% (Figure 5c,d), which confirm again that Na + in the FPS/GPNC electrode is a pseudocapacitive-dominated process. Such a high proportion of pseudocapacitance endows FPS/GPNC with superior rate performance.…”
Section: Study Of Diffusion Kinetics Of the Fps/gpnc Electrodesupporting
confidence: 57%
“…The CV curves at 0.2–3 mV s –1 are displayed in Figure a, where the shift of peak with the rise of scan rate means polarization increase. Based on the relation of the peak current and scan speed i = av b , b values can be calculated as 0.97, 0.83, 0.77, and 0.99, revealing that the Na + diffusion in the FPS/GPNC electrode is a pseudocapacitive-dominated process (Figure b). , The proportion of pseudocapacitance at different scan rates can be calculated according to i = k 1 v + k 2 v 1/2 , in which k 1 v and k 2 v 1/2 are related to pseudocapacitance and the diffusion process, repspectively. , The proportion of pseudocapacitance at the scan rates of 0.2–3 mV s –1 were calculated to be 71.6–92.2% (Figure c,d), which confirm again that Na + in the FPS/GPNC electrode is a pseudocapacitive-dominated process. Such a high proportion of pseudocapacitance endows FPS/GPNC with superior rate performance.…”
Section: Resultsmentioning
confidence: 99%
“…utilized HRTEM to identify a change in the interlayer spacing of their sodium manganese oxide cathode from 0.574 to 0.543 nm upon the intercalation of nitrogen‐containing species (Figure 3). [ 20 ] Similar to these works, many other studies have also used HRTEM to investigate the interlayer spacing of a layered material, [ 12d–f,13a,c–e,g,15,16,21 ] which often changes upon intercalation, thus acting as indirect evidence for intercalation. HRTEM also allows for directly identifying intercalant atoms in the interlayer spacing, with Chen et al.…”
Section: Overview Of Characterization Methods For Intercalantsmentioning
confidence: 98%
“…MnO 2 was deposited on TiC/C via KMnO 4 decomposition, while N doping was processed by NH 3 treatment at low temperature. Li et al designed a N-doped Na 2 Mn 3 O 7 (N-NMO) in combination with sodium pre-intercalation and nitrification strategies [55]. In the first step, they used a chemical reaction involving KMnO 4 , C 6 H 12 O 6 , and NaKC 4 H 4 O 6 to synthesize rugbytype MnCO 3 particles as precursors.…”
Section: Calcination Treatmentmentioning
confidence: 99%
“…Wang et al employed a mechanical cell grinder for doping Na + into MnO 2 and obtained a Na 0.44 MnO 2 cathode, which had a large specific surface area[67]. In 2022, Li et al reported a N-doped Na 2 Mn 3 O 7 cathode that displayed a capacity of 300 mAh•g −1 at a current density of 0.2 A•g −1 , which even retained a capacity of 100 mAh•g −1 at 10 A•g −1[55]. The modification principle was that the doping of sodium ions could enlarge the interlayer spacing and serve as a pillar to stabilize the host structure.…”
mentioning
confidence: 99%